2012
DOI: 10.1016/j.elecom.2012.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Facile template-free electrochemical preparation of poly[N-(2-cyanoethyl)pyrrole] nanowires

Abstract: a b s t r a c t a r t i c l e i n f oIn this paper the first synthesis of poly[N-(2-cyanoethyl)pyrrole] (PPyEtCN) in a nanowire morphology is reported. The method employed is a facile, one step electrochemical growth, which does not require the use of any templates or surfactants. Using optimised conditions the nanowires nucleate to give a homogeneous film across the electrode surface, with lengths of approximately 2 μm and diameters of approximately 150 nm. Structural information on the nanowires was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The electrolyte mixture (LiClO 4 (20 mM)/(NH 4 )H 2 PO 4 (100 mM)) was chosen as previous studies regarding nanowire formation have indicated that this type of system promotes the growth of PPy nanowires in the direction perpendicular to the electrode surface. ,, However, to the best of our knowledge, this is the first report utilizing this type of electrolyte system to form hollow PPy-based microstructures. It has been proposed that the role of the HPO 4 2– or H 2 PO 4 – anions during electrochemical deposition of PPy nanowires is to control the vertical growth by acting as a scaffolding agent through H-bonding between the PPy chains .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The electrolyte mixture (LiClO 4 (20 mM)/(NH 4 )H 2 PO 4 (100 mM)) was chosen as previous studies regarding nanowire formation have indicated that this type of system promotes the growth of PPy nanowires in the direction perpendicular to the electrode surface. ,, However, to the best of our knowledge, this is the first report utilizing this type of electrolyte system to form hollow PPy-based microstructures. It has been proposed that the role of the HPO 4 2– or H 2 PO 4 – anions during electrochemical deposition of PPy nanowires is to control the vertical growth by acting as a scaffolding agent through H-bonding between the PPy chains .…”
Section: Resultsmentioning
confidence: 99%
“…24,35,41 However, to the best of our knowledge, this is the first report utilizing this type of electrolyte system to form hollow PPy-based microstructures. It has been proposed that the role of the HPO 4 2− or H 2 PO 4 − anions during electrochemical deposition of PPy nanowires is to control the vertical growth by acting as a scaffolding agent through Hbonding between the PPy chains.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the micro/nanostructures may be damaged during the removal process of the hard template method. Hence, more attention has been paid on template-free (also called soft template or molecule template) methods for the preparation of micro/nanostructured PPy. The template-free method is usually realized by self-assembly of surfactant ions in the solution which do not need to be removed after the polymerization.…”
Section: Introductionmentioning
confidence: 99%